Effect of brief heat treatments performed between 650 and 850 °C on corrosion behaviour of a lean duplex stainless steel. (May 2015) - Zanotto, F.; Grassi, V.; Merlin, M.; Balbo, A.; Zucchi, F.
Highlights: Brief-time heat treatments within 650–850 °C were performed on LDX2101®. The microstructural modifications due to the performed heat treatments were analysed. Electrochemical tests were conducted to evaluate the effect on LDX2101® corrosion resistance. Susceptibility to pitting and IGC strongly increased for certain time–temperature conditions. A correlation between microstructural modifications, E pitt. and DL-EPR test results was observed. Abstract: In this study the effect of brief heat treatments within the 650–850 °C range on pitting corrosion and intergranular corrosion resistance of a lean duplex stainless steel was investigated. Pitting potentials ( E pitt .) and critical pitting temperature (CPT) were determined in sodium chloride solutions. The degree of sensitisation (DOS) to intergranular corrosion (IGC) was evaluated by DL-EPR method application. The most critical treatment conditions were observed at 650 °C and at 750 °C. A recovery of the pitting and IGC resistance of the studied lean duplex was noted at 850 °C due to the redistribution of chromium towards the depleted zones.